Pediatric autoimmune neuropsychiatric disorders associated with streptococcal infections and gut microbiota composition: what do we know? - Tagi, Veronica Maria; Tosi, Martina; Greco, Ilenia Pia; Stucchi, Eliana; Verduci, Elvira; Zuccotti, Gianvincenzo (Frontiers in Nutrition, 2025)
Post-streptococcal autoimmune neuropsychiatric disorders (PANDAS) are a group of pathological condition characterized by sudden-onset obsessive-compulsive and tic disorders following beta-hemolytic Streptococcus group A (GAS) infection, hypothesized to be caused by autoimmune mechanisms targeting the basal ganglia. Scant literature is available regarding the microbiota composition in children with PANDAS, however few studies support the hypothesis that streptococcal infections may alter gut microbiota composition in these patients, leading to chronic inflammation that may impact the brain function and behavior. Notable changes include reduced microbial diversity and shifts in bacterial populations, which affect metabolic functions crucial for neuroinflammation. Elevated serum levels of sNOX2-dp and isoprostanes indicate oxidative stress, while the presence of lipopolysaccharides (LPS) may contribute to neuroinflammation. The aim of this narrative review is to explore the link between PANDAS and gut microbiota composition. The potential connection between gut microbiota and neuropsychiatric symptoms in PANDAS might suggest the importance of dietary interventions, such as promoting the Mediterranean diet and fiber intake, to reduce the inflammatory state of this patients and therefore improve their outcome.